Xenogeneic dentin matrix as a scaffold for biomineralization and induced odontogenesis. (14th May 2021) - Li, Hui; Ma, Bo; Yang, Hefeng; Qiao, Jia; Tian, Weidong; Yu, Riyue
Abstract: Commonly recognized mechanisms of the xenogeneic-extracellular matrix-based regenerative medicine include timely degradation, release of bioactive molecules, induced differentiation of stem cells, and well-controlled inflammation. This process is most feasible for stromal tissue reconstruction, yet unsuitable for non-degradable scaffold and prefabricated-shaped tissue regeneration, like odontogenesis. Treated dentin matrix (TDM) has been identified as a bioactive scaffold for dentin regeneration. This study explored xenogeneic porcine TDM (pTDM) for induced odontogenesis. The biological characteristics of pTDM were compared with human TDM (hTDM). To investigate its bioinductive capacities on allogeneic dental follicle cells (DFCs) in the inflammation microenvironment, pTDM populated with human DFCs were co-cultured with human peripheral blood mononuclear cells (hPBMCs), and pTDM populated with rat DFCs were transplanted into rat subcutaneous model. The results showed pTDM possessed similar mineral phases and bioactive molecules with hTDM. hDFCs, under the induction of pTDM and hTDM, expressed similar col-I, osteopontin and alkaline phosphatase (ALP) (all expressed by odontoblasts). Whereas, the expression of col-I, dentin matrix protein-1 (DMP-1) and bone sialoprotein (BSP) were down-regulated when cocultured with hPBMCs. The xenogeneic implants inevitably initiated Th1 inflammation (up-regulated CD8, TNF-α, IL-1 β, etc) in vivo . However, the biomineralization of pre-dentin and cementum were still processed, and collagen fibrils, odontoblast-like cells, fibroblasts contributed to odontogenesis. Although partially absorbed at 3 weeks, the implants were positively expressed odontogenesis-related-proteins like col-I and DMP-1. Taken together, xenogeneic TDM conserved ultrastructure and molecules for introducing allogeneic DFCs to odontogenic differentiation, and promoting odontogenesis and biomineralization in vivo . Yet effective immunomodulation methods warrant further explorations.